(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
The development of this multimedia learning is motivated by the problem of learning, where teachers only use printed books as the main learning media in the classroom. Students tend to feel bored and less interested in following lessons using printed books that only contain text and images. This research aims to produce valid and practical multimedia learning products that can be used in the learning process. The type of research used is research and development, also known as Research and Development (R&D). The development model used is the 4D model, which consists of four main stages: define, design, development, and disseminate. The product validity test was conducted by 4 validators, namely 2 material validators and 2 media validators. The product trial was conducted on 20 eighth-grade students of SMP Negeri 5 Linggo Sari Baganti with the aim of determining the practicality of the developed product. The results of the material validation by 2 material validators obtained an average score of 4.93 with the category "very valid." The results from the assessment by 2 media validators obtained an average score of 4.45 with the category "very valid." The results of the media practicality test obtained an average score of 4.45 with the category "very practical." Based on the results of the validity and practicality tests, it can be concluded that the IPA learning multimedia on the "Cell Specialization" material for 8th-grade junior high school produced is valid and practical, thus it can be used in the learning process